Significance of postgrowth processing of ZnO nanostructures on antibacterial activity against gram-positive and gram-negative bacteria - Mehmood S (Dove Medical Press, 2015)
Shahid Mehmood,1 Malik A Rehman,1 Hammad Ismail,2 Bushra Mirza,2 Arshad S Bhatti11Center for Micro and Nano Devices, Department of Physics, COMSATS Institute of Information Technology, 2Department of Biochemistry, Faculty of Biological Sciences, Quaid-i-Azam University, Islamabad, PakistanAbstract: In this work, we highlighted the effect of surface modifications of one-dimensional (1D) ZnO nanostructures (NSs) grown by the vapor–solid mechanism on their antibacterial activity. Two sets of ZnO NSs were modified separately – one set was modified by annealing in an Ar environment, and the second set was modified in O2 plasma. Annealing in Ar below 800°C resulted in a compressed lattice, which was due to removal of Zn interstitials and increased O vacancies. Annealing above 1,000°C caused the formation of a new prominent phase, Zn2SiO4. Plasma oxidation of the ZnO NSs caused an expansion in the lattice due to the removal of O vacancies and incorporation of excess O. Photoluminescence (PL) spectroscopy was employed for the quantification of defects associated with Zn and O in the as-grown and processed ZnO NS. Two distinct bands were observed, one in the ultraviolet (UV) region, due to interband transitions, and other in the visible region, due to defects associated with Zn and O. PL confirmed the surface modification of ZnO NS, as substantial decrease in intensities of visible band was observed. Antibacterial activity of the modified ZnO NSs demonstrated that the surface modifications by Ar annealing limited the antibacterial characteristics of ZnO NS against Staphylococcus aureus. However, ZnO NSs annealed at 1,000°C or higher showed a remarkable antibacterial activity against Escherichia coli. O2 plasma–treated NS showed appreciable antibacterial activity against both E. coli and S. aureus. The minimum inhibition concentration was determined to be 0.5 mg/mL and 1 mg/mL for Ar-annealed and plasma-oxidized ZnO NS, respectively. It was thus proved that the O content at the surface of the ZnO NS was crucial to tune the antibacterial activity against both selected gram-negative (E. coli) and gram-positive (S. aureus) bacterial species.Keywords: oxygen defects, oxygen plasma processing, annealing, photoluminescence spectroscopy